Clinical significance and peculiarities of succinate dehydrogenase B and hypoxia inducible factor 1α expression in parasympathetic versus sympathetic paragangliomas. Issue 1 (14th December 2018) - Bernardo‐Castiñeira, Cristóbal; Sáenz‐de‐Santa‐María, Inés; Valdés, Nuria; Astudillo, Aurora; Balbín, Milagros; Pitiot, Ana S.; Jiménez‐Fonseca, Paula; Scola, Bartolomé; Tena, Isabel; Molina‐Garrido, María‐José; Sevilla, María‐Agustina; Beristein, Elena; et al.
Abstract: Background: Succinate dehydrogenase subunit B (SDHB) immunohistochemistry was considered a valuable tool to identify patients with inherited paraganglioma/pheochromocytoma (PGL/PCC). However, previous studies jointly analyzed 2 related but clinically distinct entities, parasympathetic head and neck paragangliomas (HNPGLs) and sympathetic PCCs/PGLs. Additionally, a role for hypoxia inducible factor‐1α (HIF‐1α) as a biomarker for succinate dehydrogenase ( SDHx )‐mutated tumors has not been studied. Here, we evaluated the utility of SDHB/HIF‐1α proteins in HNPGLs and PCCs/PGLs as clinically useful biomarkers. Methods: The SDHB/succinate dehydrogenase subunit A (SDHA)/HIF‐1α immunohistochemistry analysis was performed in 158 genetically defined patients. Results: Similarly to PCCs/PGLs, SDHB immune‐negativity correlated with SDHx ‐mutations in HNPGLs ( P < .0001). The HIF‐1α stabilization was associated with SDHx ‐mutations in HNPGLs ( P = .020), not in PCCs/PGLs ( P = .319). However, 25% of SDHx ‐HNPGLs lacked HIF‐1α positive cells. Conclusion: As in PCCs/PGLs, SDHB immunohistochemistry in HNPGLs is a valuable method for identification of candidates for S DHx ‐genetic testing. On the contrary, although SDHx mutations may favor HIF‐1α stabilization in HNPGLs, this is not a clinically useful biomarker.